2012
DOI: 10.1021/ed200685p
|View full text |Cite
|
Sign up to set email alerts
|

Online Video Tutorials Increase Learning of Difficult Concepts in an Undergraduate Analytical Chemistry Course

Abstract: Educational technology has enhanced, even revolutionized, pedagogy in many areas of higher education. This study examines the incorporation of video tutorials as a supplement to learning in an undergraduate analytical chemistry course. The concepts and problems in which students faced difficulty were first identified by assessing students' homework assignments and exam responses. Then, a tutorial video clip aimed at that specific knowledge point was designed by the instructor using the Camtasia software packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 8 publications
3
133
0
7
Order By: Relevance
“…However, surprisingly few studies have discussed the various methods for teaching this out-ofclass content. Some studies have shown benefits of video tutorials (e.g., He et al 2012;Kay and Kletskin 2012), and indeed video tutorials or lectures seem to be the most common method. However, only one systematic, controlled comparison has been made between various preclass content delivery methods to determine which is most effective for student learning (Moravec et al 2010), and in this study, the instructors only implemented three flipped class sessions in an otherwise non-flipped semester to investigate performance differences between students taught outside of class via video lectures versus readings.…”
Section: Variety Of Strategies For Out-of-class Content Learningmentioning
confidence: 99%
“…However, surprisingly few studies have discussed the various methods for teaching this out-ofclass content. Some studies have shown benefits of video tutorials (e.g., He et al 2012;Kay and Kletskin 2012), and indeed video tutorials or lectures seem to be the most common method. However, only one systematic, controlled comparison has been made between various preclass content delivery methods to determine which is most effective for student learning (Moravec et al 2010), and in this study, the instructors only implemented three flipped class sessions in an otherwise non-flipped semester to investigate performance differences between students taught outside of class via video lectures versus readings.…”
Section: Variety Of Strategies For Out-of-class Content Learningmentioning
confidence: 99%
“…(He, Swenson, y Lents, 2012) El uso de videos mejoró el desempeño de alumnos en un curso de química. Chen y Yan (Chen y Yan, 2016) La multitarea puede prevenirse e intervenirse con diferentes estrategias.…”
Section: Resultados Positivos Autorunclassified
“…To address this, a modified flipped-classroom methodology was employed 13,14 . Basic concept introductions, that would have been provided prior to the guided inquiry exercises, were developed into brief video lectures administered online.…”
Section: Third Year (Ay 2012-2013)mentioning
confidence: 99%